Promoting Philosophy for Children (P4C) in teaching Reading - Rizka Safriyani; Ali Mustofa (Universitas PGRI Madiun, 2021)
Philosophy for Children is an educational approach that emphasizes philosophical inquiry as a central component of the learning process. Critical thinking is cultivated through the use of reasoned moves to construct arguments. This study aims to look into how fairy tales can teach students about philosophy while also teaching them to read. This qualitative study is based on a case study at one of Surabaya's primary schools. As part of the research, two teachers participated. The data was gathered through interviews and document analysis. The findings showed that the students in the study used their own experiences to speculate and hypothesize about the activities of fictional characters. Implications and suggestions were also made